2015
DOI: 10.1186/s12917-015-0583-6
|View full text |Cite
|
Sign up to set email alerts
|

The shadows of a ghost: a survey of canine leishmaniasis in Presidente Prudente and its spatial dispersion in the western region of São Paulo state, an emerging focus of visceral leishmaniasis in Brazil

Abstract: BackgroundVisceral leishmaniasis is an emerging zoonosis and its geographic distribution is restricted to tropical and temperate regions. Most of the individuals infected in Latin America are in Brazil. Despite the control measures that have been adopted, the disease is spreading throughout new regions of the country. Domestic dogs are involved in the transmission cycle and are considered to be the main epidemiologic reservoir of Leishmania infantum (syn. L. chagasi). Our aim was to determine the prevalence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 22 publications
0
21
1
3
Order By: Relevance
“…canis prevalence rates higher than those observed in Carmo da Mata have also been reported. Some studies in São Paulo showed E. canis infection prevalence of 75.3% in Ilha Solteira (Paulan et al, 2013), 78% in Jaboticabal (Oliveira et al, 2008), and 66.5% in Presidente Prudente (D' Andrea et al, 2015). These studies report a significant difference when compared to the prevalence noted in Carmo da Mata.…”
Section: Discussionmentioning
confidence: 89%
“…canis prevalence rates higher than those observed in Carmo da Mata have also been reported. Some studies in São Paulo showed E. canis infection prevalence of 75.3% in Ilha Solteira (Paulan et al, 2013), 78% in Jaboticabal (Oliveira et al, 2008), and 66.5% in Presidente Prudente (D' Andrea et al, 2015). These studies report a significant difference when compared to the prevalence noted in Carmo da Mata.…”
Section: Discussionmentioning
confidence: 89%
“…de São Paulo (LAZ et al, 2009). Outro estudo desenvolvido na mesma região onde avaliaram a prevalência de Leishmaniose Canina (LC), bem como a dispersão espacial da doença na região, indicou o movimento da doença através dos municípios dessa região do Estado de São Paulo em direção à fronteira do estado com o Estado do Paraná (D'ANDREA et al, 2015).…”
Section: Resultsunclassified
“…Despite the measures adopted by public authorities to control VL throughout São Paulo state, there is evidence that the disease is spreading at an alarming rate throughout the western region [4, 12, 13]. Since 2009, RH has been a reference center for the diagnosis and treatment of children thought to be infected with VL in the RRAS11 region.…”
Section: Discussionmentioning
confidence: 99%